Integrating Islamic Pedagogical Values into Digital Literacy: Evidence from Teacher Education Students at Muhammadiyah Universities in Indonesia - Wahyuningsih; Maria Martini Aba; Pratama Benny Herlandy; Pratiwi Dwi Warih Sitaresmi; Rimayasi; Husamah; Akhsanul In’am (The Indonesian Institute of Science and Technology Research, 2026)
The rapid expansion of digital technologies has transformed higher education and intensified the need for digital literacy competencies that extend beyond technical proficiency to encompass ethical, critical, and value-oriented dimensions. Within Islamic higher education institutions, integrating Islamic pedagogical values into digital literacy development is increasingly important, particularly for prospective teachers who will shape future learning environments. This study investigates teacher education students’ perceptions of technology use in digital literacy, examines their understanding of Islamic pedagogical values in digital learning practices, and identifies opportunities and challenges for value-based digital literacy development. A quantitative cross-sectional survey was conducted among 256 students from Muhammadiyah universities across western, central, and eastern regions of Indonesia. Data were collected using a structured questionnaire encompassing three constructs: digital literacy, educational technology, and Islamic pedagogy. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that the integration of educational technology and Islamic pedagogical values significantly influences students’ perceptions of digital learning (β = 0.532), while positive perceptions subsequently contribute to higher levels of digital literacy (β = 0.413). The results suggest that ethical and value-based technology integration plays a critical role in strengthening students’ digital competencies. Although challenges remain in critical information evaluation and the consistent implementation of value-oriented digital learning programs, students demonstrate strong potential for ethical and creative technology use. The study highlights the importance of systematically embedding Islamic pedagogical values into digital literacy initiatives within teacher education programs.